2006
DOI: 10.1152/ajplung.00057.2005
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cells increase secretion of matrix metalloproteinases from human lung fibroblasts in vitro

Abstract: . Red blood cells increase secretion of matrix metalloproteinases from human lung fibroblasts in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 51 publications
2
22
0
5
Order By: Relevance
“…Zymography revealed constitutive expression of the proform of MMP-2 (gelatinase) in cultures of HFL-1 cells, as has been previously reported for this cell type (19,20,34). Trace levels of processed MMP-2 were also detectable in the presence of HMC-1 cells, and higher levels in the presence of pHMC.…”
Section: Discussionsupporting
confidence: 79%
“…Zymography revealed constitutive expression of the proform of MMP-2 (gelatinase) in cultures of HFL-1 cells, as has been previously reported for this cell type (19,20,34). Trace levels of processed MMP-2 were also detectable in the presence of HMC-1 cells, and higher levels in the presence of pHMC.…”
Section: Discussionsupporting
confidence: 79%
“…39 We now showed that TGF-b2-induced a-SMA expression and MLC phosphorylation in RPE cells are inhibited by both 17b-estradiol and progesterone. Moreover, both TGF-b2-induced fibronectin production and expression of MMPs, which mediate remodeling of the ECM and contribute to collagen gel contraction, 40 were also attenuated by these female sex hormones in RPE cells. These various effects of female sex hormones may thus give rise to inhibition of the contraction of proliferative fibrocellular membranes stimulated by TGF-b in PVR.…”
Section: Discussionmentioning
confidence: 99%
“…However, co-culture of fibroblasts and monocytes results in the activation of pro-MMP-2 [17,55]. Among other factors, neutrophil elastase is also known to augment the conversion of the 72-kDa form of MMP-2 to the 66-kDa form in lung fibroblasts [55,56]. …”
Section: Discussionmentioning
confidence: 99%